TGF-β1 genetic variants predict clinical outcomes of HPV-positive oropharyngeal cancer patients after definitive radiotherapy - Tao, Ye (Clin Cancer Res, 2018)
PURPOSE: Transforming growth factor-β1 (TGF-β1) plays a critical role in inflammation and immune responses and treatment response and survival. TGF-β1 variants may affect its expression level or functional efficiency, thus modifying tumor status and survival in HPV-positive squamous cell carcinoma of the oropharynx (SCCOP). EXPERIMENTAL DESIGN: We determined tumor HPV16 status and genotyped three TGF-β1 polymorphisms in 564 incident SCCOP patients treated with radiotherapy or chemoradiation. Univariate and multivariable Cox models were used to evaluate the associations between the three polymorphisms and survival. RESULTS: Overall, 85% of patients (482 of 564) had HPV16-positive SCCOP. We found that TGF-β1 rs1982073 had statistically significant associations with survival, while TGF-β1 rs1800469 and TGF-β1 rs1800471 did not. Patients with TGF-β1 rs1982073 CT/CC variant genotypes had significantly better overall, disease-specific, and disease-free survival compared with those with the corresponding common homozygous TT genotype (all log-rank: P <0.001). Furthermore, these genotypes were significantly associated with an approximately 5 times reduced risk of overall death, death owing to disease, and recurrence after multivariable adjustment. Moreover, the stratified analyses by tumor HPV status indicated that the significant effects of TGF-β1 rs1982073 polymorphism on survival were found among HPV16-positive SCCOP patients only. Finally, the functional relevance of these variants was further characterized. CONCLUSIONS: Our findings support that the TGF-β1 rs1982073 polymorphism plays a significant role in the prognosis of SCCOP, especially in HPV16-positive SCCOP patients treated with chemoradiation. Prospective studies with larger sample sizes are needed to confirm these findings.